Single cell gel electrophoresis assay: sensitivity of peripheral white blood cells in human population studies - Srám, R J; Podrazilová, K; Dejmek, J; Mracková, G; Pilcík, T (Mutagenesis, 1998)
The single cell gel electrophoresis assay (Comet assay) was selected as a biomarker of exposure to evaluate the impact of air pollution and lifestyle variables on hospitalized pregnancies in two districts with different air pollution levels in northern (Teplice) and southern (Prachatice) Bohemia. The hypothesis was that the DNA damage detected as single strand breaks would be generally higher in the district with higher air pollution levels. To undertake the study we enrolled 322 pregnancies in Teplice and 220 in Prachatice. Venous and cord blood were analysed using the original alkaline Comet assay procedure with lysis for 60 min, unwinding for 40 min and electrophoresis for 24 min. We also used a modified procedure in which unwinding was prolonged to 60 min and electrophoresis to 40 min. Peripheral white blood cells (WBC) were analysed using an image analyser system. When we analysed the results obtained for mothers and their children no differences were found between polluted and control districts. The prolongation of alkali unwinding and electrophoresis did not increase sensitivity of the assay. No effects of prematurity, ethnicity, smoking or GSTM1 polymorphism were observed for any of the Comet parameters. Multiple regression analyses were performed for the European population (n = 285). A statistical model was fitted to determine the relationship between the Comet parameters of mothers and their children. According to our results it seems that the Comet assay was not a particularly sensitive technique to determine the effects of environmental pollution at the DNA level if peripheral WBC are used.
Keywords: Electrophoresis, Agar Gel; polycyklické aromatické uhlovodíky; novorozenec; Infant, Newborn; surveillance populace; výsledek těhotenství; Pregnancy; Humans; Leukocytes; elektroforéza v agarovém gelu; oprava DNA; buněčné extrakty; Female; Pregnancy Outcome; lidé; Polycyclic Aromatic Hydrocarbons; Air Pollutants; DNA Repair; látky znečišťující vzduch; ženské pohlaví; Cell Extracts; těhotenství; Czech Republic; poškození DNA; DNA Damage; Population Surveillance; Česká republika; leukocyty